2017
DOI: 10.1177/0300060517705476
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of dental plaque and gingivitis within the dental arches

Abstract: ObjectiveThe natural accumulation of supragingival plaque on surfaces of human teeth is associated with gingival inflammation and the initiation of common oral diseases. This study evaluated the distribution of dental plaque and gingivitis scores within the dental arches after prophylaxis.MethodsAdult subjects from the Dharwad, India area representing the general population who provided written informed consent were scheduled for screening. Healthy subjects over the age of 18 years, not currently requiring any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 24 publications
6
31
0
1
Order By: Relevance
“…The Silness and Löe plaque index (1964) was used to record the dental plaque in the sample studied. [18][19][20] The plaque index's score is determined based on the amount of dental plaque at the gingival margin, which is assessed by passing a WHO probe across the gingival margin.…”
Section: Methodsmentioning
confidence: 99%
“…The Silness and Löe plaque index (1964) was used to record the dental plaque in the sample studied. [18][19][20] The plaque index's score is determined based on the amount of dental plaque at the gingival margin, which is assessed by passing a WHO probe across the gingival margin.…”
Section: Methodsmentioning
confidence: 99%
“…A significant association finding could be due to posterior teeth being subjected to threefold-higher occlusal forces than the anterior teeth [37]. Posterior regions are also known to be at a higher risk of dental plaque accumulation compared to anterior regions [38] and plaque accumulation is associated with gingival inflammation and the initiation of several oral diseases that could lead to failure of dental implant.…”
Section: Implant Locationmentioning
confidence: 99%
“…Studies have shown that plaque accumulation is greater on lingual surfaces of teeth and on molars in comparison with anterior teeth. 2,3 Supragingival plaque is also more common on interproximal surfaces of teeth than on vestibular surfaces. In order to reduce the retention of plaque in interdental spaces, it is necessary to use daily additional accessories, such as dental floss and interdental brushes.…”
Section: Introductionmentioning
confidence: 99%